FLOUTING AND VIOLATION OF MAXIMS IN “A MAN CALLED OTTO” MOVIE - Ramadanti, Salma Salsabila; Insani, Hanifa Mutiara; Rodliya, Zakiya; Hilyati, Rahma Alya; Sari Sujatna, Eva Tuckyta (Journal of Linguistic Phenomena, 2024)
The application of the maxim principle can improve the efficiency and effectiveness of the conversations. Grice’s four cooperative principles of maxims allow us to assume that the people having a conversation are working together to create an effective conversation. This research aims to identify the most frequent flouting and violations of maxims committed by the characters in “A Man Called Otto” movie and to determine the factors that cause these flouting and violations. By applying a qualitative approach, the results show that all types of maxims are flouted and violated in the movie. The study argues that the causes of the flouting and violations are lacking of understanding, and avoiding a certain topic, especially on the maxim of quality and relation. Focus on the topic, respond appropriately, and provide accurate and truthful information are the keys to effective and honest communication that remains relevant, coherent, and conducive.